Imagined Economies - Real Fictions - Fischer, Jessica (Edition Kulturwissenschaft, 2020)
The way we conceptualise the economy and ourselves as homo economicus has profound consequences for our lives. The contributions to this anthology take debates about the financial crisis, about recent austerity measures or about the Brexit referendum a step further. A common denominator of these dynamics are underlying ideas of »the economy«. Each author identifies a facet of Britain's imagined economies. They connect seemingly separate fields such as finance and fiction in order to better understand current political changes. In addition, the book offers an urgently needed interdisciplinary view on the performative power of economic thought - and in this respect moves far beyond merely British perspectives.